2011
DOI: 10.1080/02615479.2010.482984
|View full text |Cite
|
Sign up to set email alerts
|

Self-reflexive Student Research and its Implications for Social Work Education

Abstract: This paper presents a thematic analysis of postgraduate social work student research on refugee and migrant experiences in Aotearoa New Zealand, collected in the last decade from one university social work programme. The focus is on the ways in which students located themselves in relation to their research, which explored diverse facets of refugee and migrant experience and was invariably connected in some way to their own experiences. Students not only learnt to conduct qualitative research, but also found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…The findings from the empirical studies confirmed that, when students engaged in experiential and practice-based learning, they underwent a paradigm shift about qualitative research (Hein, 2004;Pratt & Dolbin-MacNab, 2003;Reisetter et al, 2003); they made personal connections with the stories shared by their interviewees (Cooper, Fleischer, & Cotton, 2012;Hein, 2004;Nash, 2011); and they also learnt to draw on their own knowledge and subjectivity to develop their identity as qualitative researchers (Barrett, 2007). Furthermore, many of the studies (see, e.g., Belcher & Hirvela, 2005;Harper et al, 2008;Hein, 2004;Henderson et al, 2008;Roulston et al, 2003) reported that the lives of students became apparent through the narratives they wrote about their learning experiences as well as the personal transformation they underwent as a result.…”
Section: The Subjective Nature Of Learning Qualitative Researchmentioning
confidence: 57%
See 2 more Smart Citations
“…The findings from the empirical studies confirmed that, when students engaged in experiential and practice-based learning, they underwent a paradigm shift about qualitative research (Hein, 2004;Pratt & Dolbin-MacNab, 2003;Reisetter et al, 2003); they made personal connections with the stories shared by their interviewees (Cooper, Fleischer, & Cotton, 2012;Hein, 2004;Nash, 2011); and they also learnt to draw on their own knowledge and subjectivity to develop their identity as qualitative researchers (Barrett, 2007). Furthermore, many of the studies (see, e.g., Belcher & Hirvela, 2005;Harper et al, 2008;Hein, 2004;Henderson et al, 2008;Roulston et al, 2003) reported that the lives of students became apparent through the narratives they wrote about their learning experiences as well as the personal transformation they underwent as a result.…”
Section: The Subjective Nature Of Learning Qualitative Researchmentioning
confidence: 57%
“…First, inquiry-based projects appear to have brought about a paradigm shift in the way students think about research (and qualitative research specifically) (Belcher & Hirvela, 2005;Benton, Androff, Barr, & Taylor, 2011;Cooper, Fleischer, & Cotton, 2012;DeLyser et al, 2013;Hein, 2004;Wang, 2013). Second, experiential learning encouraged students to make connections between their research and their professional development (Benton et al, 2011;Breidenstein, 2002;Harper et al, 2008;Nash, 2011;Roulston et al, 2008;Wang, 2013). Third, it elicited affective reflections, personal journeys of learning (Belcher & Hirvela, 2005;Breidenstein, 2002;Harper et al, 2008;Hein, 2004;Henderson et al, 2008;Nash, 2011;Roulston, deMarrais, & Lewis, 2003;Roulston et al, 2008;Wang, 2013), and intimate connections with research participants (Cooper, Fleischer, & Cotton, 2012;Nash, 2011).…”
Section: Theme 1: Experiential Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflexivity is the awareness of oneself, as well as the critical awareness of one's practice and its context (Nash, 2011). The reflexive researcher makes a critical connection between their own life experience, their professional learning, and what they are doing, with the intention to improve their practice (Nash, 2011).…”
Section: A Self-reflexive Qualitative Approachmentioning
confidence: 99%
“…Reflexivity is recognized as the awareness of oneself and critical awareness of one's practice and its context (Nash, 2011). In terms of social work, it is argued that,…”
Section: Reflexivitymentioning
confidence: 99%